Management of effluents and waste from pharmaceutical industry in Minas Gerais, Brazil (Brazilian Journal of Pharmaceutical Sciences, 2012)
Today the management of solid waste and wastewater is a major concern for humanity. In the last decade, traces of pharmaceuticals have been reported in the water cycle and have raised concerns among regulators, water suppliers and the public regarding the potential risks to human health. This study evaluated solid waste management in the state of Minas Gerais and concluded that the main fate of hazardous waste has been incineration, while the non-hazardous waste has been recycled or sent to landfills. However, complaints to the Environmental Agency - FEAM have indicated that a significant number of companies just send their hazardous wastes to landfills or even to garbage dumps, thus highlighting the urgent need for adequate waste management in Minas Gerais. Most of the pharmaceutical companies in Minas Gerais use conventional wastewater treatment. Mass spectrometry with electrospray ionization (ESI-MS) showed that the treatment routes adopted by the two 2 selected pharmaceutical industries were not effective enough since residues and degradation products of antibiotics were detected. The physicochemical analysis of the effluents showed variability in their characteristics, which may influence their treatability. The degradation assay with Fenton's reagent stood out as a promising route in achieving a higher removal capacity compared to the conventional treatment. This study contributes to enhancing our knowledge of the management of wastewater as well as of solid waste from the pharmaceutical industry in Minas Gerais and points out the need for further research.